Osteogenic Potential of Human Umbilical Cord Mesenchymal Stem Cells on Coralline Hydroxyapatite/Calcium Carbonate Microparticles - A. G. E. Day; W. R. Francis; K. Fu; I. L. Pieper; O. Guy; Z. Xia (Stem Cells International)
Coralline hydroxyapatite/calcium carbonate (CHACC) is a biodegradable and osteoconductive bone graft material with promising clinical performance. CHACC has been shown to support proliferation and osteogenic differentiation of human bone marrow mesenchymal stem cells (MSCs) in vitro and demonstrated to work as a functional scaffold for bone formation in vivo. Umbilical cord matrix is a more accessible and abundant tissue source of MSCs, but its osteogenic capacity in comparison to human bone marrow when cultured on CHACC has not yet been demonstrated. In this study, we assessed the osteogenic differentiation capacity of human MSCs, isolated from bone marrow and umbilical cord matrix and characterised by flow cytometry, when cultured on 200–300 μm CHACC granules. The 3D cultures were characterised by brightfield and scanning electron microscopy (SEM). Osteogenic potential was assessed by immunocytochemistry and qPCR for key markers of bone differentiation (alkaline phosphatase, runx2, type I collagen, and osteocalcin). By day 1, the MSCs had enveloped the surface of the CHACC granules to form organoids, and by day 7, cells had proliferated to bridge nearby organoids. Extracellular matrix deposition and osteogenic differentiation were demonstrated by MSCs from both tissue sources at day 21. However, MSCs from bone marrow demonstrated superior osteogenic differentiation capability compared to those from umbilical cord matrix. In conclusion, it is possible to culture and induce osteogenic differentiation of umbilical cord matrix MSCs on CHACC. Further research is required to optimise the osteogenicity of umbilical cord matrix MSCs to release their full potential as a readily available, accessible, and abundant tissue source for bone tissue engineering.